Technical efficacy and safety of CT-guided transforaminal periradicular infiltration using CT foot switches and MPR images - Saba, Luca; Saba, Francesco; Dagan, Robert; De Filippo, Massimo; Marcy, Pierre Yves (Acta Biomedica Atenei Parmensis, 2022)
PURPOSE:To demonstrate the technical efficacy and safety of CT-guided transforaminal periradicular infiltration in the treatment of the radicular pain without surgical intervention, using CT foot switches and MPR images.MATERIALS AND METHODS:Four hundred and eighty two patients (286 males and 196 females, age range 27-71 years, mean age 56 years) with a unilateral or bilateral radiculopathy who underwent CT-guided transforaminal periradicular infiltration without surgical intervention, were retrospectively selected in the period from January 2019 to February 2020.  Patients who had received surgery for herniated disc or laminectomy, patients with a previous vertebral fractures, and patients with inflammatory syndrome or risk of bleeding were excluded.RESULTS:There were no major or minor clinically relevant complications. Many patients a marked reduction or resolution of pain after the CT-guided infiltration (P